Describing the voice of online bullying: An analysis of stance and voice type in YouTube comments. (March 2022) - McCambridge, Laura
Abstract: In this article, I analyze the expression of stance in YouTube comments responding to a speech by Greta Thunberg addressing the 2019 United Nations Climate Action Summit. I use quantitative and qualitative analysis of explicit stance features (including attitude markers, boosters, hedges, self-mentions, and reader addresses) in order to characterize the voice type that commenters construe and examine how this voice type potentially functions as a tool for social influence. The analysis shows that the comments include continual emphatic and emotive attitude marking, almost exclusively evaluating Thunberg herself (e.g., her authenticity, cognitive ability, gender and youth), rather than directly evaluating her ideas about climate change. Commenters' evaluations drew on common vocabulary, abbreviations, symbols, and in-group references, which were boosted for example through repetition, capitalization, expletives, and superlatives. As the evaluations were almost uniformly uncivil, positioning Thunberg as a figure of ridicule and hate, I argue that they constitute a recognizable bullying voice that has become common on social media polylogues, especially those concerned with news or politics. This voice type seems to function as a means of constructing a sense of collective identity and purpose, and as an overt show of group power. The ridicule is co-constructed by commenters as a mass social judgement, with the 'we' of the commenters consisting of 'everyone', albeit with terms of address more typically used for boys/men.